A silver lining for disadvantaged youth on the apprenticeship market: an experimental study of employers' hiring preferences - Wilson, Anna [Verfasser] (My University, 2021)
"In dual vocational education and training (VET) systems, school-leavers in their mid-teens who wish to pursue vocational certificates through in-firm apprenticeships are subjected to the training providers’ quite selective hiring-processes. Previous research shows that youth with weak school performances are one of the groups that have the largest difficulties being hired as apprentices. Less investigated in the literature is what employer characteristics that are conducive for their willingness to hire a disadvantaged apprentice: both on the level of the organisation and of the recruiter. I draw on organisational and institutional literature and on person-organisation fit and ethical decision-making theory to formulate expectations regarding the preferences of the organisations and recruiters. The applied method is a factorial survey experiment administered to in-firm vocational trainers with recruitment authority in the commercial occupation in Switzerland. The findings show that public sector employers are more lenient towards candidates with weaker academic achievements than employers in the private sector. Moreover, respondents with a more egalitarian outlook on the access to vocational training for disadvantaged youths tend to lower their thresholds for the candidates’ academic achievements." (author's abstract; BIBB-Doku)
Keywords: P 1.7 Benachteiligte; I 2.2.1 Westeuropa; Berufsausbildung; Bewerberauswahl; Arbeitgeber; Benachteiligter Jugendlicher; Ausbildungschance; Öffentlicher Dienst; Privatwirtschaft; Schweiz